PPCP degradation by UV/chlorine treatment and its impact on DBP formation potential in real waters. (1st July 2016) - Yang, Xin; Sun, Jianliang; Fu, Wenjie; Shang, Chii; Li, Yin; Chen, Yiwei; Gan, Wenhui; Fang, Jingyun
Abstract: The ultraviolet/chlorine (UV/chlorine) water purification process was evaluated for its ability to degrade the residues of pharmaceuticals and personal care products (PPCPs) commonly found in drinking water sources. The disinfection byproducts (DBPs) formed after post-chlorination were documented. The performance of the UV/chlorine process was compared with that of the UV/hydrogen peroxide (UV/H2 O2 ) process in treating three types of sand-filtered natural water. Except caffeine and carbamazepine residues, the UV/chlorine process was found to be 59–99% effective for feed water with a high level of dissolved organic carbon and alkalinity, and 27–92% effective for water with a high ammonia content. Both chlorine radicals and hydroxyl radicals were found to contribute to the observed PPCP degradation. The removal efficiencies of chlorine- and UV-resistant PPCPs such as carbamazepine and caffeine were 2–3 times greater than in the UV/H2 O2 process in waters not enriched with ammonia. UV/chlorine treatment slightly enhanced the formation chloral hydrate (CH), haloketone (HK) and trichloronitromethane (TCNM). It reduced haloacetonitrile (HAN) formation during the post-chlorination in comparison with the UV/H2 O2 process. In waters with high concentrations of ammonia, the UV/chlorine process was only 5–7% more effective than the UV/H2 O2 process, and it formed slightly more THMs, HKs and TCNM along with reduced formation of CH and HAN. The UV/chlorine process is thus recommended as a good alternative to UV/H2 O2 treatment for its superior PPCP removal without significantly enhancing DBP formation. Graphical abstract: Highlights: The degradation of ten PPCPs and formation of DBPs in real water by UV/chlorine AOP are evaluated. UV/chlorine AOP enhanced PPCP removal by taking advantage of both hydroxyl and chlorine radicals. UV/chlorine with post-chlorination did not greatly enhance DBP formation compared to UV/H2 O2 .